Quality of factor XI activity testing in North American Specialized Coagulation Laboratories. (14th May 2015) - Zantek, N. D.; Hsu, P.; Meijer, P.; Smock, K. J.; Plumhoff, E. A.; Refaai, M. A.; Van Cott, E. M.
Summary: Introduction: The performance of factor XI activity (FXI) by laboratories in the North American Specialized Coagulation Laboratory Association proficiency testing program was analyzed. Methods: Over 10 years (2003–2013), 80 samples were distributed; 33–55 laboratories participated per exercise providing 3833 total responses. Analysis was performed on numeric results and qualitative classification of results. Results: The sample FXI levels ranged from 3.8 to 154.0 IU/dL. The overall interlaboratory average coefficient of variation (CV%) was 17.5%; the CV was higher for a sample with low (3.8 IU/dL) FXI. Results were correctly classified as abnormal (100%) for a sample with 3.8 IU/dL FXI and normal/borderline normal (97.7%) for 45 samples with 80 to < 140 IU/dL FXI. The classification was heterogeneous for samples with FXI of 50 to < 80 IU/dL. Six specimens were repeat‐tested from 2007 to 2013. The mean FXI was not significantly different in laboratories using the same method on both exercises, suggesting good intralaboratory precision over time. Univariate analysis of data from 2011 to 2012 did not find a consistent significant difference among the activators, analyzers, calibrators, and FXI‐deficient plasmas. Conclusion: Laboratories generally performed well in assessment of FXI based on interlaboratory precision when FXI >30 IU/dL and on classification of samples with very low or normal FXI.